EngageUC: Developing an Efficient and Ethical Approach to Biobanking Research at the University of California. Issue 4 (10th January 2015) - Garrett, Sarah B.; Koenig, Barbara A.; Brown, Arleen; Hult, Jen R.; Boyd, Elizabeth A.; Dry, Sarah; Dohan, Daniel; in collaboration with UC BRAID
Abstract Biorepositories, or biobanks, provide researchers with access to biological samples and associated data in support of translational research. Efficient operation and ethical stewardship of biobanks involves coordinated efforts among multiple stakeholders including researchers who manage and use the repository, institutional officials charged with its oversight, and patients and volunteers who contribute samples and data. As advancements in translational research increasingly involve more data derived from larger numbers of diverse samples, the size and governance challenges facing biorepositories have grown. We describe an approach to developing efficient and ethical biobank governance that includes all major stakeholders. This model provides a pathway for addressing the technical and ethical challenges that must be resolved to ensure biorepositories continue to support translational research.